2018
DOI: 10.1371/journal.pone.0196025
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based cerebral biomarkers in preeclampsia: Plasma concentrations of NfL, tau, S100B and NSE during pregnancy in women who later develop preeclampsia - A nested case control study

Abstract: ObjectiveTo evaluate if concentrations of the neuronal proteins neurofilament light chain and tau are changed in women developing preeclampsia and to evaluate the ability of a combination of neurofilament light chain, tau, S100B and neuron specific enolase in identifying neurologic impairment before diagnosis of preeclampsia.MethodsA nested case-control study within a longitudinal study cohort was performed. 469 healthy pregnant women were enrolled between 2004–2007 and plasma samples were collected at gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…In our study, median CSF concentrations of tau protein and the phospho-tau/tau ratio were significantly lower in women with PE and HELLP syndrome than in healthy controls. This is in agreement with recently reported diminished CSF tau and phospho-tau-181 protein concentrations in patients with placental dysfunction 14,15 . During normal pregnancy there is an increase in tau protein concentrations 16 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, median CSF concentrations of tau protein and the phospho-tau/tau ratio were significantly lower in women with PE and HELLP syndrome than in healthy controls. This is in agreement with recently reported diminished CSF tau and phospho-tau-181 protein concentrations in patients with placental dysfunction 14,15 . During normal pregnancy there is an increase in tau protein concentrations 16 .…”
Section: Discussionsupporting
confidence: 93%
“…The increased BBB permeability reported by both Warrington et al (2014) and Clayton et al (2018) , is partly supported by clinical studies which demonstrated that in women developing preeclampsia, blood levels of S100B, neuronal specific enolase (NSE) and neurofilament light chain (NfL), three markers of cerebral injury, were higher than those observed in women with normal pregnancies ( Bergman et al, 2018 ). Indeed, another report showed that in preeclamptic women, the levels of S100B and NSE were still high 1-year post-partum, suggesting that the alterations in the integrity of the BBB are manifest for a substantial period of time following delivery ( Bergman et al, 2016 ).…”
Section: Endothelial Dysfunction At the Brain In Pregnancy-related DImentioning
confidence: 88%
“…Preeclampsia is associated with impaired systemic endothelial function ( Roberts et al, 1989 ) and, in the brain of preeclamptic women, this endothelial dysfunction presents in the form of impaired integrity of the BBB ( Bergman et al, 2018 ), which is apparently maintained even post-partum ( Bergman et al, 2016 ). The influence of endothelial dysfunction on drug disposition in the brain has been studied in disease states, including stroke ( Huang et al, 2017 ) however there is a lack of studies investigating the effect of endothelial dysfunction on brain drug disposition in pregnancy-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Serum concentrations of tau have been proven to predict 6 months cerebral outcome after cardiac arrest in a pilot study [100]. Two studies have shown that concentrations of NfL are increased at the end of pregnancy but before onset of disease in women developing preeclampsia [101,102] and one of these studies also showed that tau was increased before onset of disease [102]…”
Section: Nfl and Tau In Preeclampsiamentioning
confidence: 99%